Enhancing In Vitro Dissolution of Ferulic Acid Through Co-Crystal Formation Using Malonic Acid and Nicotinamide Co-formers - Setyawan, Dwi; Soraya, Yasmin; Ekowati, Juni; Winantari, Agnes Nuniek; Rani, Karina Citra; Kanzaffa, Firly Afnauriza Tedja; Pujiono, Ferry Eko (Science and Technology Indonesia, 2025)
Ferulic acid is categorized as a Biopharmaceutical Classification System (BCS) class II drug, which exhibits low solubility in water (0.91 mg/mL). The formation of a co-crystal using malonic acid and nicotinamide as co-formers by the microwave irradiation method is an approach to enhance its solubility and dissolution. This study aims to evaluate the effect of co-crystal formation using these two co-formers at a 1:1 molar ratio on the solubility and dissolution of ferulic acid. The result emphasizes the formation of new peaks and peak shifting compared to the pure materials characterized from the Fourier Transform Infrared (FT-IR) spectrum. Moreover, the Differential Scanning Calorimetry (DSC) thermogram exhibits the differences in the co-crystal melting point compared to the pure drug and co-former, indicating the alteration of molecular structure on the crystal lattice of ferulic acid caused by the strong interaction between supramolecular homomer and heteromeric synthon. The formation of a new crystalline phase is also observed from the X-ray Diffraction (XRD) diffractogram, suggesting the formation of a different phase from its co-crystal component. The morphology characterization using Scanning Electron Microscope (SEM) revealed that the ferulic acid crystal habit changes into different forms, which is acclaimed as a co-crystal formation. The results of this study also disclosed that the co-crystal formation of ferulic acid significantly enhances ferulic acid solubility and dissolution characteristics compared to the pure drug and physical mixture (p < 0.05). The enhancement of solubility is 11.85% and 10.39% for ferulic acid–malonic acid and ferulic acid–nicotinamide co-crystal, respectively. Moreover, the dissolution rate of ferulic acid increases 3.50-fold and 3.61-fold from the formation of those co-crystals. Therefore, the formation of ferulic acid–malonic acid as well as ferulic acid–nicotinamide co-crystals in a 1:1 molar ratio by the microwave irradiation method is effective in improving ferulic acid solubility and dissolution.